Hearsay is not excluded: A history of natural history - Dove, Michael R. (London Yale University press, 2024)
For millennia, the field of natural history promoted a knowledgeable and unifying view of the world. In contrast, the modern rise of narrow scientific disciplines has promoted a dichotomy between nature and culture on the one hand and between scientific and folk knowledge on the other. Drawing on the fields of anthropology, history, and environmental science, Michael R. Dove argues that the loss of this historic holistic vision of the world is partly to blame for contemporary environmental degradation and science skepticism.